The Influence of Learning Media Using the Assemblr Edu Application on Student Learning Interest in Class V Science Subjects at SD Palembang - Muhammad Rizky; Al Ihwanah; Muhammad Aldri Putra Pratama; Ayu Muthmainnah; Masayu Mutiah (Innovative: Journal Of Social Science Research, 2023)
This study aims to see the influence of the Assembly Edu application on students' learning interests in the fifth grade of elementary school 226 Palembang. This study used quantitative methods with a pre-experimental type with Group Pretest-Posttest Design. The data showed that in the paired sample t-test, the significance value was 0.005, < 0.05; the significance value of the 2-tailed was 0.082,>0.05; the average pretest score was 78.75, and the post-test was 81.13. The results show an influence of learning media using the Assembler Edu application on students' learning interests, although it is insignificant.